Pitting Corrosion and Passivation of Zr/HCl 1.0 M Electrodes: The Effect of the Pre-Immersion in Molibdate Solutions - Giannetti,B.F. (2003)
The aim of this paper is to evaluate the use of molibdate solutions for pre-treatments of zirconiun surfaces. Zirconium electrodes were held immersed in molibdate solutions for predetermined time intervals. With the subsequent determination of the pitting nucleation potential and the analysis of the surface morphology, it was possible to evaluate the effect of the molibdate concentration and of the solution pH on the pitting corrosion processes. Among the most important results, two are worthy of attention: (i) for all pH values, the immersion of zirconium electrodes in molibdate solutions hinders the pitting corrosion process of the metal, shifting the pitting nucleation potential to more positive values, (ii) the more pronounced shifts of the pitting nucleation potential were observed in alkaline solutions with high molibdate concentration and in acid solutions with low molibdate concentration; this effect was attributed to the adsorption of different species formed at different pH values.